ОПТИМІЗАЦІЯ ЛІКУВАННЯ ЖІНОК З ХРОНІЧНИМ ЕНДОМЕТРИТОМ ЯК РЕЗЕРВ ПІДВИЩЕННЯ ФЕРТИЛЬНОСТІ (World Science, 2018)
The worsening demographic situation encourages the search for new reserves to improve reproductive potential. The maximum incidence of chronic endometritis (97.6%) is 26-35 years old - the most important in the implementation of reproductive function. The lack of a single concept for the pathogenesis of HE, the purge of clinical manifestations impedes the creation of well-grounded therapy in women of childbearing age. The aim of the study was to increase the effectiveness of treatment of patients with confirmed chronic endometritis in order to restore fertility. It is proved that the use of the scheme, which includes antibacterial (doxycycline 100 mg orally 2 times a day and metronidazole 500 mg 2 times a day for 14 days in one menstrual cycle) and cyclic progestogen (didrogesterone at a dose of 20 mg per day with 15 to 25 days of the menstrual cycle - within three months), therapy can restore the morpho-functional endometrium potential by 88% compared with the initial rates.